A new process for success management: bringing order to a typically ad-hoc area - Varajão, João (2018)
It is a fact that an organization's success is closely linked with its projects' success. Although there are many studies in literature that focus on different aspects of project success like, for instance, the success factors or the criteria for success assessment, there are only few studies that mention the processes required for success evaluation. Guides and standards, such as PMBOK 5 or ISO 21500:2012, are not exceptions. Given the high importance and complexity of the evaluation of the projects' success, in this article is presented a systematic process model for success management, customizable both for waterfall and agile methodologies.